The Concept of System for Automated Scientific Literature Reviews Generation - Teslyuk, Anton (Computational Science – ICCS 2020, 2020)
We present a concept of system which is aimed to create a literature review of scientific articles having a small sketch of statements as the input. Key elements of the system include transformer-based BERT encoder, deep LSTM decoder and a loss function which combines auto-encoder loss and forces generated summaries to be in the input text domain. We propose to use PMC open access subset for model learning.